Development and initial psychometric validation of a patient-reported outcome measure for Crohn's perianal fistula: the Crohn's Anal Fistula Quality of Life (CAF-QoL) scale. Issue 9 (3rd December 2020) - Adegbola, Samuel O; Dibley, Lesley; Sahnan, Kapil; Wade, Tiffany; Verjee, Azmina; Sawyer, Rachel; Mannick, Sameer; McCluskey, Damian; Bassett, Paul; Yassin, Nuha; Warusavitarne, Janindra; Faiz, Omar; et al.
Abstract : Introduction: Crohn's perianal fistulas are challenging for patients and clinicians. Many do not respond to available treatments and despite recommendations by a global consensus, there are currently no specific patient-derived quality of life tools to measure response to treatment. We present a new validated patient-reported outcome measure (PROM) for this complicated disease phenotype. Methods: A draft questionnaire was generated using unstructured qualitative patient interviews on the experience of living with Crohn's perianal fistula, a nationwide multidisciplinary consensus exercise, a systematic review of outcomes assessing medical/surgical/combined treatment and a patient and public involvement day. Psychometric properties were assessed including construct validity (by comparison with the Hospital Anxiety and Depression Scale (HADS) and the UK Inflammatory Bowel Disease Questionnaire (UK-IBDQ)), and reliability and responsiveness was assessed by test–retest analysis. Results: Data from 211 patients contributed to development of a final 28-item questionnaire. The Crohn's Anal Fistula Quality of Life (CAF-QoL) demonstrated good internal consistency (Cronbach's alpha 0.88), excellent stability (intraclass correlation 0.98) and good responsiveness and construct validity, with positive correlation with the UK-IBDQ and HADS. Conclusion: The CAF-QoL scale is ready for use as a PROM in research and clinical practice. It complements objective clinical evaluation of fistula by capturing impact on the patient.